2017
DOI: 10.1177/1753425916686170
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity of macrophages in canine histiocytic ulcerative colitis

Abstract: Histiocytic ulcerative colitis (HUC) is a chronic enteropathy which most notably occurs in Boxer dogs and French bulldogs. The inflamed mucosa is hallmarked by large, foamy, periodic acid-Schiff (PAS)-positive macrophages infiltrating the colonic mucosa. As little is known about their origin and phenotype, an immunohistochemical study was performed using different macrophage markers. Generally, canine colonic macrophages showed high expression of ionised calciumbinding adaptor molecule 1 and MHC class II. In c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 82 publications
2
22
0
Order By: Relevance
“…We found that healthy dogs had a higher number of CD163 + than CAL + cells both in villi and crypts, which is consistent with previous observations in dogs with histiocytic ulcerative colitis and CE. 21,32 Furthermore, CD163 + was decreased in dogs with IRE prior to treatment compared with CTRL dogs as reported recently in dogs with CE where information about treatment response is unknown. 21 Response to treatment in both FRE and IRE dogs was characterized by an increase in CD163 + (significant in IRE dogs).…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…We found that healthy dogs had a higher number of CD163 + than CAL + cells both in villi and crypts, which is consistent with previous observations in dogs with histiocytic ulcerative colitis and CE. 21,32 Furthermore, CD163 + was decreased in dogs with IRE prior to treatment compared with CTRL dogs as reported recently in dogs with CE where information about treatment response is unknown. 21 Response to treatment in both FRE and IRE dogs was characterized by an increase in CD163 + (significant in IRE dogs).…”
Section: Discussionsupporting
confidence: 60%
“…Most studies in dogs to date have assessed intestinal Mϕ using CAL expression only, except for two recent studies assessing CAL with other putative Mϕ markers in dogs with histiocytic ulcerative colitis or chronic enteropathy. 11,12,14,21,32…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2,3,5 In canine cases, macrophage heterogeneity suggests a difference in function compared with healthy individuals. 6…”
Section: Discussionmentioning
confidence: 99%
“…T‐cells, FOXP3+ cells, B‐cells and macrophages, were detected using anti‐CD3 (1:50; rat anti‐human, CD3‐12; Moore Lab; Davis, California), anti‐FOXP3 (1:25; rat anti‐mouse/rat, FJK‐16S; Thermo Fisher Scientific; San Diego, California), anti‐Pax‐5 (1:50; 24/Pax‐5; BD Biosciences; San Jose, California), and anti‐CD204 (1:400; mouse anti‐human, SRA‐E5; Cosmo Bio; Carlsbad, California), respectively. The anti‐CD3 and ‐FOXP3 clones are stated as canine cross‐reactive by their manufacturers, while the anti‐Pax‐5 and ‐CD204 have shown canine cross‐reactivity in several previous studies . The ImmPRESS horseradish peroxidase (HRP) polymer detection kit was used for primary antibody detection (anti‐mouse IgG, MP‐7452; anti‐rat IgG, MP‐7444; Vector; Burlingame, CA), and Vector NovaRed HRP substrate kit (Vector; Burlingame, California) was used for chromogen development.…”
Section: Methodsmentioning
confidence: 99%